Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Draw a model of the equation below -4x + y = 2

Sagot :

-4(0) + 0 = 2 ??

That's not possible! See

-4(0)=0

-> 0=2

Suppose we want to find the value of y when x=0

-> -4(x=0)+y = 2

-> -4*(0) + y = 2

-> 0 + y=2

-> y=2

Now, what if y=0? What would the value of x be? Let's find out!

-4x + (y=0) = 2

-> -4x + 0 = 2

-> -4x=2

-> -4x (-1/4) = 2(-1/4)

-> x=-2/4

-> x= -1/2